The Development of Nursing Job Performance Model in The Implementation of Integrated Management of Childhood Illness (Imci) in Surabaya - Rekawati Susilaningrum; Chriswardani Suryawati; Septo Pawelas Arso (Jurnal Ners, 2012)
Introduction: MTBS is a comprehensive approaches for child illnes and one of the way to reduce an infant and under ﬁ ve years morbidity and mortality rateas well as appropriately to apply in public health center. In fact, MTBS has not been implemented as procedure guidance. The objective of the study was to examie the implementation of MTBS viewed from Van Meter and Van Horn model as basic measurement and the goal of policy, the sources of policy, a communication among organisation and the implementation of MTBS.Method: The study was qualitative design. Data were collected by in depth interview. Six Nurse and midwife were recruited as a sample by purposive sampling. Informant triangulation were head of PHC and head of deputy health services. Analysis was by means of content analysis.Result showed that the written and indicator of basic measurement and goal policy was not available yet. Sources of policy, namely health.Result: For the health workers was sufﬁcient and they have a good competency to carry out MTBS and have workload focus on three types. Fasilities was no room, form was difﬁcult to provide, instruments and medication was sufﬁcient available, but there was no speciﬁc funding. Communication was carried out only on the training program by MTBS fascilitator. Characteristic of beaurocracy structure (SOP) consists of preparation, implementation, eporting and recording.There was no speciﬁc preparation, it only an introduction dessimination was done. The implementation was not as modul and the form of MTBS was not used anymore. The implementation of MTBS lack support from Public Health center and Health Care District of Surabaya. Healh worker unmotivated to implement MTBS.Conclusio: the implementation of MTBS lack support from health worker, Public Health Center and Health Care District of Surabaya.It is recomended that Health Care District & Public Health Center cooperatively should have commitment to assess the implementation of MTBS in Surabaya.